KARAKTERISTIK BETON ASPAL DENGAN SUBSTITUSI AGREGAT LIMBAH INDUSTRI PENGOLAHAN BIJI BESI (STEEL SLAG) - Nunung Martina; Rinawati Jakfar (Jurnal Poli-Teknologi, 2013)
Hot mix asphalt concrete with substitution of waste metal processing ( steel slag ) aggregate is the result of residual waste processing or a crust of iron ore furnace , visually shaped as hard lumps and irregularly shaped rock , has a specific gravity > 2.9, steel slag considered as a heavy aggregate. According to the sii 0052-80, steel slag that had less than 27% destroyed sections through a 1.7 mm sieve when tested with los angeles engines, can be used as aggregate. A 50% substitution variation of steel slag aggregate provides characteristics of asphalt concrete mixtures that is eligible to the bina marga 1998 requirement, with the optimum value at the variation of 50 % steel slag to coarse aggregate, with the stability value of 1016.00 kgf, melting value ( flow ) has the lowest value of 3:32 mm , marshall quetion optimum at 306.30 , cavities in aggregate > 16 % , the cavity filled with asphalt > 65 % , the cavity in a mixture of 3 % - 5 % . Keywords : steel slag , filler , marshall test , temperature , asphalt concrete